Handbook of research on approaches to alternative entrepreneurship opportunities - Dantas, Jose Guilherme Leitao 1955-; Carvalho, Luísa Cagica 1970- (IGI Global, 2019)
""This book explores key developments in entrepreneurship types such as academic entrepreneurship, corporate entrepreneurship, cultural entrepreneurship, and entrepreneurship in high-tech sectors"--Provided by publisher"--
Description based on title screen (IGI Global, viewed 03/03/2020)
Keywords: Businesswomen; Entrepreneurship; Organizational learning; Strategic planning